Maximizing Recovery in the Postpartum Period: A Timeline for Rehabilitation from Pregnancy through Return to Sport - Rachel Selman; Kate Early; Brianna Battles; Misty Seidenburg; Elizabeth Wendel; Susan Westerlund (International Journal of Sports Physical Therapy)
Increased participation and duration in sport has become commonplace for women with their involvement often including the transition to motherhood in the peak of their athletic careers. No rehabilitation models that assess the full spectrum of pregnancy to postpartum have been developed for women to assist in safe exercise progressions that reduce postpartum symptoms and optimize performance during the return to full activity. Referral to physical therapy both in the prenatal and postnatal period is currently not considered standard of care to reduce prevalence of symptoms such as musculoskeletal pain, diastasis recti, and pelvic floor dysfunction which may ultimately interfere with physical activity and performance. This commentary presents a timeline and suggested progression for exercise participation to improve awareness of the musculoskeletal changes that occur after labor and delivery. The concepts covered may increase the understanding of how to manage pregnant and postpartum athletes from a musculoskeletal perspective and serve as a starting point for establishing appropriate and guided rehabilitation for safe return to sport after childbirth.